LPS- and LTA-Induced Expression of IL-6 and TNF-α in Neonatal and Adult Blood: Role of MAPKs and NF-κB - Lutz Koch; David Frommhold; Kirsten Buschmann; Navina Kuss; Johannes Poeschl; Peter Ruef (Mediators of Inflammation)
As nuclear factor kappa B (NF-κB) and mitogen-activated protein kinases (MAPKs) seem to be critical mediators in the inflammatory response, we studied the effects of lipopolysaccharide (LPS) and lipoteichoic acid (LTA) on (a) the activation of NF-κB and MAPKs and (b) the expression of tumor necrosis factor alpha (TNF-α) and interleukin 6 (IL-6) with or without the specific inhibitors of these intracellular signal transduction pathways in neonatal cord and adult blood. TNF-α and IL-6 concentrations showed a sharp increase in the supernatants of cord and adult whole blood after stimulation. TNF-α concentrations were significantly higher, whereas IL-6 concentrations were tendentially lower in adult blood after stimulation. Stimulation with LPS or LTA resulted in a significantly decreased activation of p38 MAPK in neonatal compared with adult blood. Although LTA failed to induce additional ERK1/2 phosphorylation, LPS stimulation mediated the moderately increased levels of activated ERK1/2 in neonatal monocytes. The addition of the p38 MAPK inhibitor SB202190 significantly decreased IL-6 and TNF-α production upon LPS or LTA stimulation. Furthermore, the inhibition of ERK1/2 was able to reduce LPS-stimulated TNF-α production in neonatal blood. We conclude that p38 MAPK as well as ERK1/2 phosphorylation is crucially involved in LPS activation and could explain the differences in early cytokine response between neonatal and adult blood.